Survival in B-Cell Primary Ocular Lymphoma 1997–2014: A Population-Based Study. (December 2018) - Liu, Deliang L; Zheng, Zhuojun J
This study sought to explore the prognostic factors in a large retrospective cohort of patients with B-cell primary ocular lymphoma (POL) from the Surveillance, Epidemiology, and End Results database. There were 2778 patients with B-cell POL whose complete clinical information was listed in the Surveillance, Epidemiology, and End Results database between 1997 and 2014. The epidemiology, therapeutic measures, and clinical characteristics were listed as descriptive statistics. Survival analysis was conducted by univariate and multivariable Cox regression models. Multivariate analysis identified age, lymphoma subtype, primary lesion, and radiation status as independent prognostic factors. For indolent lymphoma, radical treatment, especially intravenous chemotherapy, should be avoided. For invasive lymphoma, chemotherapy combined with full orbital irradiation is recommended. Radiotherapy alone or in combination with chemotherapy is superior to chemotherapy alone. These differences were statistically significant (p<0.05). Radiation brings benefits, with tolerable neurotoxicity, to patients with invasive B-cell POL. Radical tumor treatment may not be needed for patients with indolent B-cell POL.